2001
DOI: 10.1002/1099-0690(200108)2001:15<2947::aid-ejoc2947>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

New Formylating Agents − Preparative Procedures and Mechanistic Investigations

Abstract: The reactivity of new formylating agents related to formamide has been investigated both experimentally and theoretically. The reaction in 1,2-dichloroethane between tris(diformylamino)methane (2) and several arenes, catalyzed by AlCl 3 or BCl 3 , was shown to proceed in good yields to afford the corresponding para-substituted aldehydes. The nature of the active electrophilic species was also investigated theoretically. Thus, the relative stability of the O-and N-protonated forms, as well as those of AlCl 3 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…C-2 is deprotonated if phenyl lithium, n-BuLi or sodium sand is used as reagent; subsequently adding DMF or N-methyformanilide yields the C-2 formylated product. [185][186][187][188][189] While C-4 is formylated when Gattermann/Adams, 151,152 Gross,190 Vilsmeier-Haack [191][192][193] or reaction methods derived thereof 194,195 are employed. Yields are in the range of 45-99%.…”
Section: Formylation Of Resorcinolsmentioning
confidence: 99%
“…C-2 is deprotonated if phenyl lithium, n-BuLi or sodium sand is used as reagent; subsequently adding DMF or N-methyformanilide yields the C-2 formylated product. [185][186][187][188][189] While C-4 is formylated when Gattermann/Adams, 151,152 Gross,190 Vilsmeier-Haack [191][192][193] or reaction methods derived thereof 194,195 are employed. Yields are in the range of 45-99%.…”
Section: Formylation Of Resorcinolsmentioning
confidence: 99%
“…Triformamide is accessible by formolysis of tris(dichloromethyl)amine ( 10 ), but tris(dichloromethyl)amine ( 10 ) itself can be viewed as a formylating reagent in the presence of Lewis acid 33,37. The compound is not ionised but is structurally closely related to the iminium chloride 1 used in Vilsmeier−Haack formylation reactions.…”
Section: Formylation Of Aromatic Compounds With Tris(dichloromethymentioning
confidence: 99%
“…The analogous reactivity of α,β‐unsaturated amides has not thus far been investigated. However, superacidic activation of the amides could involve their O ‐protonation16,17 or O ‐complexation18 with Lewis acid, with subsequent additional protonation of C=C (or C≡C) bonds. Thus, it was recently shown that cinnamanilide 5 cleanly undergoes intramolecular cyclization in triflic acid to give quinolinone 6 in good yield 19.…”
Section: Introductionmentioning
confidence: 99%